Alveolar Ridge Preservation Using a Novel Synthetic Grafting Material: A Case with Two-Year Follow-Up - Peter Fairbairn; Minas Leventis; Chas Mangham; Robert Horowitz (Hindawi Limited, 2018)
This case report highlights the use of a novel in situ hardening synthetic (alloplastic), resorbable, bone grafting material composed of beta tricalcium phosphate and calcium sulfate, for alveolar ridge preservation. A 35-year-old female patient was referred by her general dentist for extraction of the mandibular right first molar and rehabilitation of the site with a dental implant. The nonrestorable tooth was "atraumatically" extracted without raising a flap, and the socket was immediately grafted with the synthetic biomaterial and covered with a hemostatic fleece. No membrane was used, and the site was left uncovered without obtaining primary closure, in order to heal by secondary intention. After 12 weeks, the architecture of the ridge was preserved, and clinical observation revealed excellent soft tissue healing without loss of attached gingiva. At reentry for placement of the implant, a bone core biopsy was obtained, and primary implant stability was measured by final seating torque and resonance frequency analysis. Histological analysis revealed pronounced bone regeneration while high levels of primary implant stability were recorded. The implant was successfully loaded 12 weeks after placement. Clinical and radiological follow-up examination at two years revealed stable and successful results regarding biological, functional, and esthetic parameters.